ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TABUNGAN RUMAH TANGGA PEDESAAN DI KECAMATAN DELANGGU KABUPATEN KLATEN - -, Sutarno (Universitas Slamet Riyadi, 2006)
ABSTRACT This study is an empirical study conducted in Delanggu District Klaten Regency, and was aimed to analyze the dominant factors contributing to rural households saving. The study employed descriptive statistics and linear regression techniques from a sample of 93 households. The dependent variable was a rural household saving devided by family size. The result indicated that using linear regression for rural households saving’s model was the best model, for 66% prediction capability of its independent variable, and there are no multicollinearity, heteroscedasticity and autocorrelation. There are 3 factors that have significant contribution to rural households saving: household income devided by family size, share consumption in total income and occupation of household head. Education of household head, young age dependency ratio and old age dependency ratio do not have considerable influence, since none of those have significant coefficients. The study recommends the necessity for intensive rural househol savings mobilization by developing rural financial institutions for saver and borrower, and reviewing agricultural credit programmes for rural household. Keywords: Rural saving domestic, domestic earnings, earnings source, consumption,